Problematising history in the public relations curriculum. (11th August 2020) - Fitch, Kate; L'Etang, Jacquie
Abstract : Purpose: The aim of this paper is to begin a conversation about historicising the public relations (PR) curriculum in universities. Design/methodology/approach: The paper discusses PR history and historiography to identify the underlying ideological and methodological influences. It considers scholarship on PR education, and the inclusion or, more often, the exclusion of history except where it serves to reinforce a narrative of steady, and apparently unproblematic, professional development. The paper reviews the presentation of history in textbooks and discusses the authors' experiences of teaching PR history. The paper concludes with a discussion of how the inclusion of history in the PR curriculum offers an important critical intervention in PR education. Findings: The PR curriculum tends to meet industry expectations around practice and skills in order to develop students as future practitioners. But this paper argues that a more historical and historiographical understanding of PR can develop in students important skills in research, analysis and interpretation. It can also introduce students to working with ambiguity and alternate perspectives. Foregrounding new histories and challenging existing histories introduce students to richer and more complex understandings of PR. It also introduces students to epistemology and ethics, and therefore offers a way to introduce critical thinking into the curriculum. Originality/value: A more historical understanding of PR develops student skills in research, analysis and interpretation as well as critical thinking.